Pendekatan Neorosains dalam Pembelajaran Membaca Al-Qur’an Untuk Anak Usia Dini - Deliana Fitriani; Sri Latifah; Alam Tarlam (JURNAL ILMIAH NUSANTARA, 2026)
arly childhood is a foundational period for all aspects of development. Therefore, this stage is the most appropriate time to provide stimulation across various developmental domains, particularly cognitive development as well as religious and moral values. One form of such stimulation is through learning the Qur’an. In this process, children not only learn to write, recognize letters, and read, but also begin to understand the content of the Qur’an, which helps develop their cognitive abilities, religious and moral values, and socio-emotional skills.This study was conducted to determine the most appropriate Qur’anic learning methods for young children from a neuroscience perspective. This approach is based on the understanding that brain development is the central driver of overall human development. Therefore, the researchers recommend that Qur’anic learning practices be aligned with neuroscience principles, including recognizing the differences between the brain development of boys and girls. Additionally, it is important to consider each child’s learning style so that educators can select the most suitable teaching methods. By doing so, every child sains equal opportunities and can more easily achieve learning objectives.